Cytotoxicity Evaluation of Self Adhesive Composite Resin Cements by Dentin Barrier Test on 3D Pulp Cellss - Ulker, Hayriye Esra; Sengun, Abdulkadir (European Journal of Dentistry, 2009)
Objectives: The aim of this study was to evaluate the effects of five self-etch dental composite resin cements on the cell viability of bovine dental papilla-derived cells.Methods: The cytotoxicity of composite resin cements (Rely X Unicem Clicker, 3M ESPE; MaxCem; KERR, PanaviaF 2.0; Kuraray, BisCem; Bisco and Bistite II DC; Tokuyama) was analyzed in a dentin barrier test device using three-dimensional (3D) pulp cell cultures. A commercially available cell culture perfusion chamber was separated into two compartments by 500 im dentin disc. The three dimensional cultures placed on a dentin disk held in place by a special biocompatible stainless-steel holder. Test materials were introduced into the upper compartment in direct contact with the cavity side of the dentin disks according to the manufacturer’s instructions. Subsequently, the pulpal part of the perfusion chamber containing the cell cultures was perfused with medium (2 ml/h). After an exposure period of 24 h, the cell survival was determined by the MTT assay. Statistical analyses were performed using the Mann–Whitney U-test.Results: In dentin barrier test, cell survival was similar with Maxcem and negative control group (P>.05), and all other tested materials were cytotoxic for the three dimensional cell cultures (P>.05).Conclusions: The significance of composite resin cements is being more important in dentistry. The cytotoxic potencies demonstrated by these materials might be of clinical relevance. Some composite resin cements include biologically active ingredients and may modify pulp cell metabolism when the materials are used in deep cavities or directly contact pulp tissue. (Eur J Dent 2009;3:120-126)
Keywords: Resin cement; Cytotoxicity; Dentin barrier test; Three dimensional cultures